Influence of the nutrient medium and the spectral composition of light on the reproduction of strawberry in vitro - M. G. Markova; E. N. Somova (Аграрная наука Евро-Северо-Востока)
The research was conducted in 2016-2017 on the basis of a meristem laboratory. Object of the research is the micro-shoots of garden strawberry the Festival variety and remontant strawberry the Brighton variety at the stages of micropropagation and rooting. The following nutrient media were studied: Murashige and Skoog (control), Murashige and Skoog modified (microelements were replaced with a corresponding dose of microfertilizer “Siliplant”) and Boxyu; LED irradiators - with a ratio in the spectrum of red, blue and white light R2: B1:W1 and R1: B1: W1, respectively, and a programmable one with a changing spectrum. A luminescent lamp with white light served as the control. The highest rate of reproduction in the cultivation of garden strawberry in vitro was obtained using the Murashige and Skoog culture medium under a LED irradiator with a R1: B1: W1 combination of red, blue and white light and the irradiator with a changing spectral composition: 6.0 and 6.2 pieces/microcutting, respectively. The highest reproduction factor of remontant strawberry was provided by cultivation on the Murashige and Skoog nutrient medium using the LED light irradiator in ratio of red, blue and white as R1:B1:W1 and the irradiator with a changing spectral composition: 3.5 and 3.2 pieces / microcutting, respectively. A rooting of micro-shoots of garden strawberry on the modified Murashige and Skoog nutrient medium and Boxyu provided a significant increase in rooting ability to 100% and 97.5%, respectively. Cultivation on the Boxyu nutrient medium has increased the rooting ability of micro-shoots of remontant strawberry to 95.0%. All the LED irradiators provided a significant increase in the rooting ability of micro-shoots: for garden strawberries - up to 96.6-100%, for remontant - up to 83.3-90.0%.